Farm Laws - Kumar, Abhishek (Trinity Law Review, 2021)
In June 2020, the Central Government presented three ordinances focusing on extensive agricultural changes in the nation. Government has expressed that the objectives of the Act are to Freeing up controls on trade, changing administrative framework, giving hindrance free trade and establishing a farmer-friendly environment. These ordinances will override all State laws in this regard. But this was all done in absence of a strong opposition and without consulting with the states, farmers and the commission agents, who are the main affected parties, resulting in a strong opposition and demand for rollback of the ordinances.